Etnografi Komunikasi Penyandang Disabilitas - Stefanus O. P. Olga; Blajan Konradus; Monika Wutun (Jurnal Communio : Jurnal Jurusan Ilmu Komunikasi, 2019)
This study aims to describe and express the ethnography of communication person with disabilities in speeches children at the Kupang branch of the Bhakti Luhur orphanage. The theory used is the theory of symbolic interaction by George Herbert Mead. Qualitative research paradigm namely ethnography of communication. Data collection techniques and data analysis used are Dell Hyms. The results of research on the type of communication events in the communication process of speechless children at the orphanage consist of two, namely communication events of speech children with nurses, communication events, children with speech impairments and teachers. The components that make up the communication events of the speechless child setting and scene, namely the location or place and time of communication of the child who is speech impaired by the nurse and teachers, participants, anyone who is involved in the communication process between a speechless child nurse and teacher, ends, the purpose of communication is the speechless child nurse and teacher, action sequences, communication forms of nurse and teachers speechless children that include verbal and nonverbal messages, key, tone of voice in the process of communication of children with speech disabilities and teachers, instrumental, the what message was conveyed through verbal and nonverbal messages, norms, regulations apply at the orphanage, genre, delivery forms such as prayer advice and the relationships of the components that make up communication events. The relationship between the communication components that make up the communication event between nurses and teachers speechless children is colored by verbal and nonverbal languages that appear in the form of statement submissions and requests. The conclusions of this study are the communications process that occurs between nurses of speechless children and teachers at the orphanage who use SPEAKING components in forming communication events.